SAXS and UV-Vis combined to Quick-XAFS monitoring of ZnO nanoparticles formation and growth - Caetano, Bruno Leonardo [UNESP]; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Briois, Valerie (Taylor & Francis Ltd, 2011)
Time-resolved X-ray absorption-fine structure (Quick-XAFS) and UV-Vis absorption spectroscopies were combined for monitoring simultaneously the time evolution of Zn-based species and ZnO quantum dot (Qdot) formation and growth during the sol-gel synthesis from zinc oxy-acetate precursor solution. The time evolution of the nanostructural features of colloidal suspension was independently monitored in situ by small angle X-ray scattering (SAXS). In both cases, the monitoring was initialized just after the addition of NaOH solution (B = [OH]/[Zn] = 0.5) to the precursor solution at 40 degrees C. Combined time-resolved Quick-XAFS and UV-Vis data showed that the formation of ZnO colloids from the zinc oxy-acetate consumption achieves a quasi-steady-state chemical equilibrium in less than 200s. Afterwards, the comparison of the ZnO Qdots size and Guinier gyration radius evidences a limited aggregation process coupled to the Qdots growth. The analysis of the experimental results demonstrates that the nanocrystal coalescence and Ostwald ripening control the kinetics of the Qdot growth.
Keywords: time-resolved X-ray absorption; UV-Visible absorption; SAXS; quantum dots formation; ZnO; sol-gel